Strategies of Integrated Islamic Schools in Realizing Quality Islamic Education - Muhamamd Akhir; Muhammad Rizki Syahputra; Zainidah Siagian (Fitrah: Journal of Islamic Education, 2025)
This study is motivated by the importance of well-planned and high-quality Islamic education management in responding to quality demands and ensuring the integration of Islamic values within school institutional practices. The study aims to analyze the design, implementation, organization, mobilization, and evaluation of quality-oriented Islamic education management strategies at Ar-Rayhan Integrated Islamic Elementary School. Employing a qualitative field research approach, data were collected through observation, in-depth interviews, and document analysis. The data were analyzed descriptively using the stages of data reduction, data display, and conclusion drawing. The findings reveal that Islamic education management at the school is carried out in a systematic and integrative manner, characterized by participatory strategic planning, consistent implementation, effective organization and mobilization of human resources through participatory leadership, and continuous evaluation encompassing managerial, pedagogical, and cultural dimensions. The study implies that sustainable quality in Islamic education can be achieved through holistic, value-oriented strategic management that actively involves all members of the school community as an integrated educational system.